Vision‐related quality of life and dependency in French keratoconus patients: Impact study. Issue 12 (December 2017) - Saunier, Valentine; Mercier, Audrey‐Elodie; Gaboriau, Thibaut; Malet, Florence; Colin, Joseph; Fournié, Pierre; Malecaze, François; Touboul, David
Abstract : Purpose : To assess the quality of life in French keratoconus patients. Setting : Fifty‐seven Keratoconus National Reference Centers across France. Design : Prospective case series. Methods : Patients completed the National Eye Institute Visual Functioning Questionnaire‐25 (NEI VFQ‐25) and a French validated questionnaire on disability and dependency from February to June 2012 when they came for an ophthalmic examination at 57 participating centers across France. An ocular examination including refraction, corneal topography, pachymetry, and slitlamp biomicroscopy was performed. The composite or global NEI VFQ‐25 score and the proportion of patients who were dependent (defined by the difficulties with activities of daily living) because of keratoconus were the main evaluation criteria in this study. Results : The study comprised 550 keratoconus patients. Women, corrected distance visual acuity worse than 20/40, steep keratometry higher than 52.0 diopters, history of surgery (corneal transplant, intrastromal corneal ring segments, or corneal crosslinking), and more severe keratoconus according to the Amsler‐Krumeich classification were associated with an increasingly negative impact on quality of life (overall scores are significantly lower). Moreover, 4.9% of participants reported having changed their jobs because of keratoconus and 7.8% received keratoconus‐related disability. Sixty‐nine (12.5%) patients reported having difficulties with activities of daily living and are considered dependent. Conclusion : Keratoconus was associated with a significant reduction in quality of life but it did not result in social exclusion.